1989
DOI: 10.1152/ajpendo.1989.256.2.e322
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of beta-endorphins on glucose homeostasis in the conscious dog

Abstract: The effects of centrally administered beta-endorphins on glucose homeostasis in the conscious dog were studied. Intracerebroventricular administration of beta-endorphin (0.2 mg/h) caused a 70% increase in plasma glucose. The mechanism of the hyperglycemia was twofold: there was an early increase in glucose production and a late inhibition of glucose clearance. These changes are explained by marked increases in plasma epinephrine (30-fold) and norepinephrine (6-fold) that occurred during infusion of beta-endorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Hashiguchi et al administered intracerebroventricularly to demonstrate the effect of central opioids on glycogen levels in peripheral tissues as we did in our study [16]. Radosevich et al practiced on dogs to demonstrate icv and iv effects of β-endorphins on blood glucose level; they reported that central administration had increased blood glucose levels whereas peripheral application did not affect glucose homeostasis [20]. Various studies also report that these effects of endogenous opioid peptides can be antagonized with naloxone in experimental conditions [21].…”
Section: Discussionsupporting
confidence: 54%
“…Hashiguchi et al administered intracerebroventricularly to demonstrate the effect of central opioids on glycogen levels in peripheral tissues as we did in our study [16]. Radosevich et al practiced on dogs to demonstrate icv and iv effects of β-endorphins on blood glucose level; they reported that central administration had increased blood glucose levels whereas peripheral application did not affect glucose homeostasis [20]. Various studies also report that these effects of endogenous opioid peptides can be antagonized with naloxone in experimental conditions [21].…”
Section: Discussionsupporting
confidence: 54%
“…In addition to ␣-MSH, POMC also is a prohormone for ␤-endorphin, a hormone which increases intake of palatable diets (7). Central administration of ␤-endorphin also produces a strainand site-dependent elevation of blood glucose and possibly insulin levels (2,37). Thus, if elevated ARC POMC expression were associated with increased ␤-endorphin production and release, this might predispose nonobese F-DIO rats to develop abnormal glucose metabolism and to eat more and gain more weight when exposed to the high corn oil and sucrose content of the HE diet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the effects of i.c.v. infusion of the endogenous opioid β-endorphin [13], the synthetic μ-opioid receptor agonist morphine [3] or DAMGO [14] on blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate central opioid stimulation and glucose control, i.c.v. infusion of opioids has been used [2,13,14], thereby simultaneously affecting multiple brain areas. Because opioid receptors are expressed throughout the brain [15], it is unclear which brain areas are responsible for the changes seen in glycaemia upon i.c.v.…”
Section: Introductionmentioning
confidence: 99%